Dirac Nodal Arc Semimetal PtSn4: An Ideal Platform for Understanding Surface Properties and Catalysis for Hydrogen Evolution. Issue 37 (13th August 2019) - Li, Guowei; Fu, Chenguang; Shi, Wujun; Jiao, Lin; Wu, Jiquan; Yang, Qun; Saha, Rana; Kamminga, Machteld E.; Srivastava, Abhay K.; Liu, Enke; Yazdani, Aliza N.; Kumar, Nitesh; et al.
Abstract: Conductivity, carrier mobility, and a suitable Gibbs free energy are important criteria that determine the performance of catalysts for a hydrogen evolution reaction (HER). However, it is a challenge to combine these factors into a single compound. Herein, we discover a superior electrocatalyst for a HER in the recently identified Dirac nodal arc semimetal PtSn4 . The determined turnover frequency (TOF) for each active site of PtSn4 is 1.54 H2 s −1 at 100 mV. This sets a benchmark for HER catalysis on Pt‐based noble metals and earth‐abundant metal catalysts. We make use of the robust surface states of PtSn4 as their electrons can be transferred to the adsorbed hydrogen atoms in the catalytic process more efficiently. In addition, PtSn4 displays excellent chemical and electrochemical stabilities after long‐term exposure in air and long‐time HER stability tests. Abstract : Putting the tin into plaTINum : The Dirac semimetal PtSn4 has a two‐dimensional layered structure. Intrinsic and stable surface states are found in the Pt layer of the PtSn4 single crystal. The p orbitals of Pt atoms of these robust surface states can deliver electrons efficiently for hydrogen reduction. PtSn4 thus acts as a benchmark electrocatalyst for hydrogen evolution.